Analysis of Human Kidney Stones Using Advanced Characterization Techniques - Jelena Brdarić Kosanović; Kristijan Živković; Vatroslav Šerić; Berislav Marković; Imre Szenti; Ákos Kukovecz; Nives Matijaković Mlinarić; Anamarija Stanković (Crystals)
A comprehensive analysis of kidney stones is essential for the future treatment of patients. Almost all of the methods available for kidney stone analysis were used in this study. The chemical analysis included powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA-DSC). Following the chemical analysis, a detailed morphological analysis was carried out using stereoscopic microscopy, scanning electron microscopy (SEM-EDX), and micro-computed tomography (micro-CT). These investigations showed that the sixteen kidney stones analyzed in detail had a heterogeneous mineralogical structure, consisting of at least two different minerals. Kidney stones consist mainly of calcium oxalate (whewellite or weddellite) but also contain significant amounts of phosphate (mainly apatite and struvite). A thorough analysis of kidney stones can determine the cause of their formation and investigate possible treatments.